Babassu Cake in Goat Diet Improves Growth Performance and Quality and Fatty Acid Profile of Meat. Issue 4 (26th February 2021) - Oliveira, Thamys P. R.; Cutrim Júnior, José A. A.; Costa, Joaquim B.; Gois, Glayciane C.; Queiroz, Mário A. Á.; Quadros, Cedenir P.; Wagner, Roger; Vendruscolo, Raquel G.; Figueirêdo Neto, Acácio; Rodrigues, Rafael T. S.
Abstract: Babassu cake (BC) is a byproduct from oil extraction from babassu palm kernels. The aim of this study is to evaluate the effect of including BC levels (0%, 6%, 12%, and 18% on a dry matter basis) in the diet of 28 kids ( n = 7 per treatment) on productive performance, and quality and profile of fatty acids (FA) of meat (loin). The inclusion of BC in the diet increases dry matter intake ( P = 0.0005), average daily gain ( P = 0.0222), slaughter body weight ( P = 0.0424) of goats, and increased fat ( P = 0.0424), unsaturated fatty acids ( P = 0.0041), monounsaturated fatty acids (P = 0.0163), and isomers of conjugated linoleic acid (rumenic acid; P = 0.0002) content and polyunsaturated fatty acids:saturated fatty acids ratio ( P = 0.0430) of meat. However, there are reductions in the levels of stearic acid ( P < 0.0001) and saturated fatty acids ( P = 0.0041) and in the thrombogenicity index ( P = 0.0219) of meat. The inclusion of BC in the goat diet improves its growth performance and the quality and fatty acid profile of meat. Abstract : Babassu cake is used to feed goats. After feedlot, animals are slaughtered and the loin is evaluated for physical–chemical analysis and fatty acid profile. The inclusion 18% babassu cake improves the profile of fatty acids and increases marbling in goat meat.